Pengaruh Lama Penyimpanan Terhadap Mutu Ikan Cakalang Asap (Katsuwonus pelamis) - Azis Husen; Ruslan A. Daeng (Agrikan: Jurnal Agribisnis Perikanan, 2018)
Moked fish is one of the processed products that can be used as raw material for processing together with the use of combinations and chemicals from fuel  combustion.  This research is to obtain the best time in the process of curing skipjack (Katsowonus pelamis) so that it can produce smoked fish meat with good quality.  The  purpose  of  this  study  was  to  determine  how  long  the  storing  capacity  of  smoked  skipjack  meat  and  its quality.  This study uses microbiological and organoleptic testing, namely to find out the color, taste, texture, aroma,  smell  by  using  statistical  analysis. Based  on  the  results  of  the  organoleptic  test  analysis  on  smoked skipjack meat on color, taste, aroma, appearance, and texture of the five treatments, the smoked fish products can  still  be  accepted  by  the  panelists  while  for  the  2nd  and  3rd day,  fish  meat  which  is  stored  seen  from  the quality  and  quality  and  taste  of  smoked  fish  has  been  contaminated  with  fungi  and  bacteria  on  the  day 4,5,6,7,8, and the 9th can not be consumed anymore, the temperature used for smoked smoked fish is 80-110 oC whereas storage in 4oC freerer and storage of smoked fish for 9 days. Microbiological testing parameters with the results of testing the Total Plate Number (ALT) for samples of smoked skipjack with three analyzes get the first sample with a small value of 31,508 while the second sample with a value of 32,905 and the third one is 35,801 so the small battery is the first sample.